The gathering storm : Eduardo Frei's revolution in liberty and Chile's Cold war - Hurtado-Torres, Sebastián, 1982- (United States in the world., 2020)
"A new interpretation of the involvement of the United States in Chilean politics in the years of Eduardo Frei's Revolution in Liberty"--